Selbstregulationen von Kindern. - Hellmich, Frank; Wernke, Stephan (Auf den Anfang kommt es an: Kompetenzen entwickeln – Kompetenzen stärken)

Optimizing Slicing of Formal Specifications by Deductive Verification - Brückner, Ingo; Metzler, Björn; Wehrheim, Heike (Nord. J. Comput.)

Model Transformations Incorporating Multiple Views - Derrick, John; Wehrheim, Heike (Algebraic Methodology and Software Technology, 11th International Conference, AMAST 2006, Kuressaare, Estonia, July 5-8, 2006, Proceedings)

Incremental Slicing - Wehrheim, Heike (Formal Methods and Software Engineering, 8th International Conference on Formal Engineering Methods, ICFEM 2006, Macao, China, November 1-3, 2006, Proceedings)

Formal Methods for Open Object-Based Distributed Systems, 8th IFIP WG 6.1 International Conference, FMOODS 2006, Bologna, Italy, June 14-16, 2006, Proceedings

Speeding Up Model-based Diagnosis by a Heuristic Approach to Solving SAT - Stein, Benno; Niggemann, Oliver; Lettmann, Theodor (AIA '06: Proceedings of the 24th IASTED International Conference on Artificial Intelligence and Applications)

Professional Learning: Erfahrung als Grundlage von Handlungskompetenz - Gruber, Hans; Harteis, Christian; Rehrl, Monika (Bildung und Erziehung)

Potentialanalysen in der Personalentwicklung--ein kritischer Diskurs - Rehrl, Monika; Harteis, Christian; Gruber, Hans (German Journal of Human Resource Management)

Der Umgang mit Fehlern als Merkmal betrieblicher Fehlerkultur und Voraussetzung fur Professional Learning - Harteis, Christian; Bauer, Johannes; Heid, Helmut (SCHWEIZERISCHE ZEITSCHRIFT FUR BILDUNGSWISSENSCHAFTEN)

Epistemological beliefs and their impact on work, subjectivity and learning - Harteis, Christian; Gruber, Hans; Lehner, Franz (Work, subjectivity and learning)

Oser, F. & Spychiger, M.(2005). Lernen ist schmerzhaft. Zur Theorie des Negativen Wissens und zur Praxis der Fehlerkultur - Harteis, Christian (SCHWEIZERISCHE ZEITSCHRIFT FUR BILDUNGSWISSENSCHAFTEN)

How to close the value gap between market and tax values - Mueller, Jens (EcoMod 2006)

Randomness and Secrecy - A Brief Introduction - Blömer, Johannes (Journal of Universal Computer Science (J.UCS))
We give a brief introduction to probabilistic encryptions. This serves as an example how randomness plays a pivotal role in cryptographic systems that satisfy advanced security concepts.

Fault Based Collision Attacks on AES - Blömer, Johannes; Krummel, Volker (Lecture Notes in Computer Science)

Wagner’s Attack on a Secure CRT-RSA Algorithm Reconsidered - Blömer, Johannes; Otto, Martin (Lecture Notes in Computer Science)

Sign Change Fault Attacks on Elliptic Curve Cryptosystems - Blömer, Johannes; Otto, Martin; Seifert, Jean-Pierre (Lecture Notes in Computer Science)

Influence of adaptive data layouts on performance in dynamically changing storage environments - Brinkmann, Andre; Effert, Sascha; Heidebuer, Michael; Vodisek, Mario (14th Euromicro International Conference on Parallel, Distributed, and Network-Based Processing (PDP'06))
For most of today's IT environments, the tremendous need for storage capacity in combination with a required minimum I/O performance has become highly critical. In dynamically growing environments, a storage management solution's underlying data distribution scheme has great impact to the overall system I/O performance. The evaluation of a number of open system storage visualization solutions and volume managers has shown that all of them lack the ability to automatically adapt to changing access patterns and storage infrastructures; many of them require an error prone manual re-layout of the data blocks, or rely on a very time consuming re-striping of all available data. This paper evaluates the performance of conventional data distribution approaches compared to the adaptive virtualization solution V:DRIVE in dynamically changing storage environments. Changes of the storage infrastructure are normally not considered in benchmark results, but can have a significant impact on storage performance. Using synthetic benchmarks, V:DRIVE is compared in such changing environments with the non-adaptive Linux logical volume manager (LVM). The performance results of our tests clearly outline the necessity of adaptive data distribution schemes.

The influence of habitual protein intake in early childhood on BMI and age at adiposity rebound: results from the DONALD Study - Günther, A L B; Buyken, Anette; Kroke, A (International Journal of Obesity)

REVIS – Reform der Ernährungs- und Verbraucherbildung in Schulen - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Zur Analyse von Unterrichtsmaterialien für die Ernährungs- und Verbraucherbildung - Methfessel, B.; Schlegel-Matthies, Kirsten (Haushalt & Bildung)